Binding of Human Single Chain Urokinase to Chinese Hamster Ovary Cells and Cloning of Hamster u-PAR - Fowler, Bruce; Mackman, Nigel; Parmer, Robert J.; Miles, Lindsey A. (Thrombosis and Haemostasis, 1998)
The plasminogen activator, urokinase (u-PA), interacts with the u-PA receptor (u-PAR) which results in enhanced plasminogen activation on cell surfaces. The u-PAR is comprised of three homologous domains of ~90 amino acids, defined by the pattern of disulfide bonds. Domain 1 (amino acids 1-87) binds the ligand. Within this domain, Y57, and a site between residues 47 and 53, have been suggested as ligand contact points. Intradomain interactions also contribute to the interaction of u-PA and u-PAR.The interaction of u-PA with its receptor exhibits some species specifity. Previous studies have shown that human u-PA does not bind to the murine u-PAR and murine u-PA does not recognize human u-PAR. However, human u-PA does interact with bovine cells with high affinity. To further examine the interaction of the human ligand with the u-PAR of a different species, we characterized the binding of human 125I single chain u-PA (scu-PA) to hamster cells. Chinese Hamster Ovary (CHO) cells bound human scu-PA with high affinity and capacity (Kd = 1.13 ± 0.8 nM; B max = 5.45 ± 0.98 × 104 sites/cell). In ligand blotting with human 125I-scu-PA, major bands migrating with apparent Mr’s of 74, 49 and 38 kDa were observed. The cDNA of hamster u-PAR was cloned and a single 1.4 kb mRNA species identified in Northern blots of CHO cell RNA. For comparison, we also cloned u-PAR cDNA from human THP-1 cells. Our human sequence was identical to those published for U937 and endothelial cells. These sequences were aligned with the published sequences for the murine, bovine and rat u-PAR’s to obtain a consensus sequence for five species. The cysteine residues could be aligned for all species. Y57, which has been suggested as a ligand contact point was also conserved across species. In addition, 5 of the 7 amino acids between amino acids 47 and 53 were conserved in all species. Gly283, the most likely glycosylphosphatidyl inositol attachment site, was also conserved in all species. The conservation of these amino acid residues across all five species, attests to their importance in u-PAR function. In addition, the results of